The genus Afrosyrphus Curran (Diptera, Syrphidae), with a description of a new species - Mengual, Ximo; Ssymank, Axel; Skevington, Jeffrey H.; Reemer, Menno; Ståhls, Gunilla (European Journal of Taxonomy, 2020)
The flower fly genus Afrosyrphus Curran, 1927 (Diptera, Syrphidae) is revised and a new species, Afrosyrphus schmuttereri sp. nov., from Kenya and Uganda is described. Diagnoses, illustrations, DNA barcodes and known distributional data are provided for the two species of this genus, as well as an identification key. A critical review of the published literature is also provided.